1998
DOI: 10.1152/physrev.1998.78.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Somatotropin in Growth and Lactation of Domestic Animals

Abstract: Impressive progress has been made during the past 15 years in our understanding of the biology of somatotropin (ST) in domestic animals. In part, this progress was sparked by advances in biotechnology that made feasible the production of large quantities of recombinant bovine ST (bST) and porcine ST (pST). The availability of recombinant bST and pST resulted in an exponential increase in investigations that explored their role in growth and lactation biology, as well as evaluated their potential for commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
236
1
25

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(273 citation statements)
references
References 157 publications
11
236
1
25
Order By: Relevance
“…Daily administration of growth hormone (GH) to growing animals can reduce adipose tissue growth by as much as 80% (for review, see [34]). The major underlying biological mechanism is a marked decrease in glucose transport and lipogenesis in adipose tissue with relatively no change in lipolysis.…”
Section: Growth Hormonementioning
confidence: 99%
See 2 more Smart Citations
“…Daily administration of growth hormone (GH) to growing animals can reduce adipose tissue growth by as much as 80% (for review, see [34]). The major underlying biological mechanism is a marked decrease in glucose transport and lipogenesis in adipose tissue with relatively no change in lipolysis.…”
Section: Growth Hormonementioning
confidence: 99%
“…The major underlying biological mechanism is a marked decrease in glucose transport and lipogenesis in adipose tissue with relatively no change in lipolysis. However, the reduction in fatty acid synthetase (FAS) gene expression (FAS being a key lipogenic enzyme) was of much greater magnitude than that of GLUT4 gene expression in pig adipose tissue following growth hormone treatment [30], although a 40% decrease in the GLUT4 protein was observed in some experiments [34]. It has thus been suggested that growth hormone affects the distribution of GLUT4 protein between plasma and intracellular membranes entry rate induces an increase in the hexosamine pathway, thereby increasing intracellular glucosamine content which inhibits GLUT4 translocation following insulin stimulation [67].…”
Section: Growth Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Sci. 68(10): 1075-1080, 2006 Growth hormone (GH) is a very important factor for livestock production [6]. GH-releasing hormone (GHRH) and somatostatin (SS) from the hypothalamus are primary factors controlling GH secretion in mammals.…”
mentioning
confidence: 99%
“…GH is released from the adenohypophysis through a series of physiological stimuli such as GH-releasing hormone (GHRH), somatostatin, glucagon, insulin, IGF-1 and IGF-2 (Etherton and Bauman 1998). At the tissue level, the pleiotropic actions of GH result from its binding to specific GH receptors (GHRs) (Wells 1996), which results in transduction of an intracellular signal (Eleswarapu et al 2008).…”
Section: Introductionmentioning
confidence: 99%